Inhibition of Pro-Inflammatory Cytokines by Metabolites of Streptomycetes-A Potential Alternative to Current Anti-Inflammatory Drugs? - Hrdý, Jiří; Súkeníková, Lenka; Petrásková, Petra; Novotná, Olga; Kahoun, David; Petříček, Miroslav; Chroňáková, Alica; Petříčková, Kateřina (Microorganisms, 2020)
Current treatment of chronic diseases includes, among others, application of cytokines, monoclonal antibodies, cellular therapies, and immunostimulants. As all the underlying mechanisms of a particular diseases are not always fully clarified, treatment can be inefficient and associated with various, sometimes serious, side effects. Small secondary metabolites produced by various microbes represent an attractive alternative as future anti-inflammatory drug leads. Compared to current drugs, they are cheaper, can often be administered orally, but still can keep a high target-specificity. Some compounds produced by actinomycetes or fungi have already been used as immunomodulators-tacrolimus, sirolimus, and cyclosporine. This work documents strong anti-inflammatory features of another secondary metabolite of streptomycetes-manumycin-type polyketides. We compared the effect of four related compounds: manumycin A, manumycin B, asukamycin, and colabomycin E on activation and survival of human monocyte/macrophage cell line THP-1. The anti-cancer effect of manucycine A has been demonstrated; the immunomodulatory capacities of manumycin A are obvious when using micromolar concentrations. The application of all four compounds in 0.25-5 μM concentrations leads to efficient, concentration-dependent inhibition of IL-1β and TNF expression in THP-1 upon LPS stimulation, while the three latter compounds show a significantly lower pro-apoptotic effect than manumycin A. We have demonstrated the anti-inflammatory capacity of selected manumycin-type polyketides.
Keywords: immunomodulation; secondary metabolites; manumycins; inflammation; Streptomyces